PENGEMBANGAN SISTEM PRESENSI MENGGUNAKAN QR CODE BERBASIS WEBSITE PADA SISWA SMK - Aryo Bagaskoro, Yoga; Wantoro, Jan (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
The attendance system in many vocational high schools (SMK) is still conducted manually, which often leads to inefficiencies, data manipulation, and loss of records. This research aims to develop a web-based student attendance system using QR Code technology to address those issues. The system was developed using the Waterfall model, comprising five stages: requirements analysis, system design, implementation, verification, and maintenance. The system was built using PHP with the CodeIgniter framework and MySQL database, and was designed to be user-friendly for both teachers and students. The results showed that the QR Code-based attendance system successfully automated the recording of student attendance, minimized errors, and generated real-time attendance reports. Blackbox Testing was used to evaluate the system’s functionality, yielding a 100% success rate. Maintenance was carried out to fix minor bugs and interface inconsistencies without altering the core features. Overall, the system enhances the efficiency and accuracy of attendance management in schools and supports the digital transformation of educational administration.